Over-deterministic method: The influence of rounding numbers on the accuracy of the values of Williams expansion terms - V. Ru풞icka; L. Malkov; S. Seitl (Fracture and Structural Integrity)
A study on the accuracy of the values of Williams expansion terms influenced by rounding numbers is presented. The results are presented taking into account a three-point bend single edge notched beam. Crack tip stress tensor components are expressed using the linear elastic fracture mechanics (LEFM) theory in this work, more precisely via its multi-parameter formulation, i.e. by Williams power series (WPS). Determination of the coefficients of the terms of this series is performed using the least squaresbased regression technique known as the over-deterministic method (ODM), for which displacements data obtained numerically in software ANSYS are taken as inputs. The values of Williams expansion terms based on the displacement data obtained are calculated by using various levels of rounding numbers and the results are compared and discussed